Managing indirect spend enhancing profitability through strategic sourcing - Payne, Joseph; Dorn, William R. (Wiley corporate F & A series, 2012)
Unique guidance for cutting costs regardless of economic conditions—without reducing headcounts Successfully reduce costs in the area of indirect spend and watch your bottom line grow. Managing Indirect Spend provides you with the knowledge and tools necessary to get it done with an overview of: the challenges faced when sourcing indirect spend categories; strategic sourcing process; tools that can help drive savings, and examples based on real world experience. This how-to guide clearly covers specific sourcing engagements and provides the details needed to source effectively. Includes